Una verdad incómoda - Marquina, Orietta (Pontificia Universidad Católica del Perú. Fondo Editorial, 2009)
The video An Unconvenient Truth (Guggenheim 2006) is analysed at the light ofthe sustainable development theories: It works as starting point for some reflections about the sense and practice of education in relation with the Global Warming phenomenon. What we need today is an education that disturbs our habits and customs,the manner we relate to nature and our expectations and concept on welfare.Bothering us and bothering others, education will friendly accommodate our life,both material and spiritual, to environment in a sustainable manner. We need an education that helps us to create new collective imaginaries to guide our daily action,both individual and in community, building new roads to sustainable development.

El video Una verdad incómoda (Guggenheim 2006) es analizado a la luz de losplanteamientos de las teorías del desarrollo sustentable, dando origen a reflexiones sobre el sentido y el quehacer educativo con relación al fenómeno del calentamiento global. Lo que necesitamos hoy en día es una educación que incomode nuestros hábitos y costumbres, nuestra forma de relacionarnos con la naturaleza y nuestras expectativas y concepto sobre el bienestar. Una educación que, al incomodarnose incomodar al otro, acomode nuestra vida y la de los demás, tanto material como espiritual, con la del medio ambiente de una manera sostenible. Una educación que nos ayude a crear nuevos imaginarios colectivos que guíennuestra acción cotidiana tanto individual y en sociedad construyendo así nuevos caminos para el desarrollo sostenible.
Keywords: Environmental Education; Sustainable Development; Education Anddevelopment; Environment; Educación ambiental; Desarrollo Sostenible; Educación y Desarrollo; Medio Ambiente; https://purl.org/pe-repo/ocde/ford#5.03.00